A necessary and sufficient condition of optimality for a class of multidimensional control problems. (23rd July 2020) - Treanţă, Savin
Abstract: In this paper, we introduce a necessary and sufficient condition of optimality for a new class of multidimensional optimal control problems governed by path‐independent curvilinear integral functionals and mixed constraints involving first‐order partial differential equations (PDEs) of m ‐flow type. Furthermore, as a consequence, we establish the equivalence between the class of (strongly) b ‐invex functionals and the class of (strongly) b ‐pseudoinvex functionals. The mathematical development in the paper is supported by illustrative examples, as well.